Elbow Instability: Anatomy, Biomechanics, Diagnostic Maneuvers, and Testing - Karbach, Lauren E. (J Hand Surg Am, 2017)
The elbow comprises a complex of bony and ligamentous stabilizers that provide both primary and secondary constraints to elbow instability. Through trauma and overuse, classic instability patterns arise by loss of these important stabilizers. The diagnosis of elbow instability can made using specific examination maneuvers and testing to diagnose the clinical pattern. This article reviews the elbow’s unique anatomy and biomechanical characteristics and these are applied when reviewing the maneuvers and testing used to diagnose elbow instability.